THE IMPACT OF ANCIENT QURANIC MANUSCRIPTS ON CONTEMPORARY LINGUISTIC AND EXEGETICAL STUDIES: AN INTERDISCIPLINARY ANALYSIS - Al Fiqri Ardiansyah; Marhamah Annazah Tambunan (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2023)
Abstract This study investigates the influence of ancient Quranic manuscripts on linguistic studies and the understanding of linguistic nuances in the Quranic text. By employing a comprehensive methodological framework that integrates philology, paleography, historical linguistics, hermeneutics, and comparative studies, this research aims to uncover the linguistic evolution and contextual adaptations of the Quran over time. The study analyzes various ancient manuscripts from the Meccan and Medinan periods, comparing them with modern Quranic texts to identify significant linguistic variations. Advanced digital tools and statistical methods are utilized to ensure precise analysis and validation of findings. Key findings include the identification of vocabulary changes, syntactic developments, and orthographic variations that highlight the dynamic nature of the Arabic language. The incorporation of insights from these ancient manuscripts into contemporary Quranic studies provides a richer, more nuanced understanding of the Quran’s message and historical context. This interdisciplinary approach not only bridges traditional and modern interpretations but also enhances the depth and relevance of Quranic exegesis in contemporary scholarship.